VD_FINDINFO HC / 2015 / 681 vom 3. Juli 2015 - VD Tribunal cantonal (2015)
EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE, DÉCISION SUR FRAIS, FRAIS D'EXÉCUTION | 106 al. 1 CPC (CH), 343 al. 1 let. e CPC (CH)